The influence of gender stereotypes on gender judgement and impression evaluation based on face and voice - Jingyu Li; Chunye Fu; Yunrui Sun (PeerJ)
The present study examined the influence of gender stereotype information on cognitive judgments and impression evaluations of faces and voices. A 2 × 2 × 2 design was employed, with Perceptual Target (Face vs. Voice), Gender Stereotype Information (Consistent vs. Inconsistent) and Gender of Perceptual Targets (Male and Female) serving as within-subject factors. The results demonstrated that when gender stereotype information was consistent with the perceptual target’s gender, response times for face gender judgments were shorter than for voice gender judgments. Nevertheless, the accuracy of gender judgments was higher for voices than faces. Furthermore, likability ratings for targets were significantly higher when gender stereotype information was consistent with the target than when it was inconsistent, for both face and voice judgments. These findings indicate that visual and auditory cues are processed differently in the context of gender judgments, thereby highlighting the distinct roles of facial and vocal information in gender perception. The current study contributes to understanding the complex interplay between gender stereotypes and multimodal social information processing.